Implementasi Kajian Kitab Lubabul Hadits dalam Pembinaan Keagamaan Jamaah Majelis Ta’lim Nurul Dholam - Ahmad Syaikhul Yasin (CV. Lentera Literasi Indonesia, 2026)
This study aims to describe the implementation of the Lubabul Hadits study as a medium for religious development among the congregation of Majelis Ta’lim Nurul Dholam at Mushola Nurul Dholam, Sidoluhur Village, Godean District, Sleman Regency, Special Region of Yogyakarta. This research employed a qualitative approach with a descriptive method. Data collection techniques included observation, interviews, and documentation. The research subjects consisted of the ustadz as the study instructor, members of the majelis ta’lim congregation, and mushola administrators selected through purposive sampling techniques. Data analysis was conducted using the Miles and Huberman model through data reduction, data presentation, and conclusion drawing, using source and technique triangulation to ensure data validity. The results showed that the implementation of the Lubabul Hadits study was carried out routinely twice a week during the month of Ramadan using traditional pesantren learning methods, namely reading the text, translating, and explaining the hadith contextually. The study received positive responses from the congregation because the material was easy to understand and relevant to daily life. In addition to improving religious understanding and worship motivation among the congregation, the study activities also played a role in strengthening social and spiritual relationships within the community. This study contributes to the development of community-based Islamic nonformal education models through contextual kitab learning traditions.